PERANCANGAN PRODUK FASHION BAGI MASYARAKAT URBAN INDONESIA DENGAN PEMANFAATAN TENUN LURIK JAWA PEDAN - Wenny Anggraini Natalia; Dian Widiawati; Agus Sachari (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2019)
The existence of Javanese Pedan lurik weaving which is one of the Indonesian cultural heritages that needs to be preserved in this modern era. Using the method of observation, visual analysis and experimentation, it is designed to revitalize fashion products by utilizing Javanese lurik woven cloth intended for Indonesian urbanites with a character of young spirit, full of locality, and love of culture. Sustainable design methods become a solution by considering the impact on the natural and social environment at each stage, which will later be related to the economy of the community. Through this article, it is hoped that it will enrich the development of fashion products with Indonesian cultural nuances that will increase the selling power of Javanese lurik woven into the wider community. In addition, using revitalized Javanese Pedan motifs and patterns that have been revitalized, it is hoped that the public will become more aware that there are still regional motifs and patterns that are still unexplored and is expected to be more known and awake sustainability.